The impact of an educational intervention on undergraduate students’ knowledge, acceptability, and willingness to pay for dapivirine vaginal ring in Nigeria's first indigenous university: a single-arm, non-randomized study - Abdulmuminu Isah; Gabriel Ezenri; Ogechi Obi; Nnamdi A. Okibe; Hadiza Usman Ma’aji; Ezinwanne J. Ugochukwu; Cynthia C. Eze; Chisom M. Amoke; Augustus Ezeodimegwu; Charles C. Idabor; Mustapha Muhammed Abubakar; Francis Iloabuchi; et al. (Discover Social Science and Health)
Abstract Background This study aimed to assess the impact of an educational intervention on knowledge, acceptability, and willingness to pay (WTP) for dapivirine vaginal ring (DPV-VR) by undergraduate female students at the University of Nigeria (UNN). Methods A cross-sectional design was adopted to obtain responses from the respondents using a validated 23-item questionnaire. A sample size of 1500 was estimated from five systematically sampled faculties. Their acceptability was accessed before and after educating them on the dapivirine vaginal ring (DPV-VR). WTP was determined in Naira (N490/$1) using contingent valuation. Descriptive statistics were used to summarize the findings, with inter-faculty comparison done with the Chi-squared test. Results 1017 students responded to the questionnaire. The modal age was 18–24 years (754 [74.1%]), and most of them (886 [87.1%]) were unmarried. More than half of the respondents had tested for HIV (531 [52.2%])), with 3 (1.5%), 3 (1.7%), 2 (0.6%), 2 (1.8%) and 1 (0.5%) student from Arts, Biological Sciences, Pharmaceutical Sciences, Social Sciences, and Veterinary Medicine, respectively, having positive results. Only 304 (29.9%) of the students had prior knowledge of DPV-VR. There was about a two-fold increase in the acceptability of the dapivirine vaginal ring (DPV-VR) (294 to 596) after the intervention (p ≤ 0.001). Most of the students (466 [45.8%]) indicated that they would be willing to pay < N410.00 for a single dapivirine vaginal ring (DPV-VR). Conclusions Many of the female students at UNN were willing to use the dapivirine vaginal ring (DPV-VR); even more after they were informed of its importance. Most of the students were willing to pay less than one dollar out-of-pocket for the ring.